2021
DOI: 10.1176/appi.ps.202000441
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Care Providers’ Attitudes Toward Telepsychiatry: A Systemwide, Multisite Survey During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has forced a rapid transition to telepsychiatry. This study examined the experience and attitudes of mental health care providers toward telehealth.Methods: At 18 centers across the United States, 819 mental health care providers completed an electronic survey about telepsychiatry use and satisfaction.Results: Overall, 73% of providers using videoconferencing and 66% using the telephone rated their experience as excellent or good. Flexible scheduling or rescheduling (77%) and timely start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
81
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 14 publications
9
81
1
1
Order By: Relevance
“…Our study shows that psychiatrists express an overall interest toward telepsychiatry in the context of the COVID-19 pandemic, corroborating previous results [ 15 ]. However, few patients were seen with telepsychiatry by responders, and a minority felt they had acquired telepsychiatry skills during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Our study shows that psychiatrists express an overall interest toward telepsychiatry in the context of the COVID-19 pandemic, corroborating previous results [ 15 ]. However, few patients were seen with telepsychiatry by responders, and a minority felt they had acquired telepsychiatry skills during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, positive attitudes toward the use of mHealth apps to help alleviate the psychosocial consequences of the pandemic were highly prevalent and associated with an objective need (e.g., more severe levels of psychological distress and higher levels of worrying). There have been also other studies which have reported that individuals have a positive attitude toward, and increasingly use, digital interventions during the current COVID-19 pandemic across the whole spectrum of public mental health provision (i.e., mental health promotion, prevention, and treatment of mental disorders) [36][37][38]49,50], and alterations of telemedicine regulations have been reported [51]. However, mHealth apps provide the opportunity of delivering lowthreshold, personalized mental health care in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been highly effective in high-income countries [4][5][6] and their use and effectiveness in LMIC has been seen across diverse settings and MH conditions [7][8][9][10][11][12][13] . There are numerous advantages to digital MH solutions, including reduced travel time, costs, and wait times, and improved access to services and information [14][15][16][17] . In some cases, they are considered an enabling and empowering form of service delivery and have increased patient and caregiver satisfaction rates 18,19 .…”
Section: Introductionmentioning
confidence: 99%